<span>(2.5×10^−10)(7×10^−6)
= (2.5 x 7) (</span>10^−10 x 10^−6)
= 17.5 x 10^-16
= 1.75 x 10^-15
answer
<span>B. 1.75×10^−15 </span>
Answer:
2
Step-by-step explanation:
it's literally 6-4 = 2
Answer:
A) 2k+4
Step-by-step explanation:
To solve for terms of x, we need to. she sure that x is on its own side while every other term is on the other side.
To start, we will cross multiply. If we have a/b=c/d, then ad=bc
We can perform the same calculation here,
6/x=3/(k+2)
6(k+2)=3x
Divide both sides by 3
2(k+2)=x
x=2k+4
2:10 and 4:20
therfor
1:5
times 5
5:25
answer is 25 minutes
Answer:D
Step-by-step explanation: